APPLICATION OF ARTIFICIAL INTELLIGENCE IN HIGHER EDUCATION MANAGEMENT: GLOBAL AND KAZAKHSTANI EXPERIENCE - Yelubay, Г.Б.; Akhmetov, Б.С.; Gnatuk, С.А.; Shuitenov, Г.Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
Modern higher education faces numerous challenges, such as the need to improve the quality of educational services, manage large volumes of data, personalize learning trajectories, and ensure accessibility. Artificial intelligence (AI) is becoming a key tool in addressing these issues by enabling process automation, outcome prediction, and support for managerial decision-making. This review focuses on analyzing previous scientific studies related to the use of AI in higher education management, with an emphasis on global experience and the experience of the Republic of Kazakhstan.